Development of liveworksheet assisted teaching materials for students' mathematical problem-solving ability - Teddy Ronny, Renata; Hidayat, Wahyu (Pusat Studi Pengembangan Pembelajaran Matematika, 2023)
Problem-solving ability is one of the hard skills that students need to solve everyday math problems. The learning model is felt to be in line with the ability to solve mathematical problems, namely the problem-based learning model because learning can be oriented to the ability to solve various problems, especially those related to the application of learning materials in everyday life. This study aims to develop teaching materials in the form of student worksheets with a problem-based learning model assisted by Liveworksheet on students' mathematical problem-solving abilities. This study used the development research method in two stages, namely preliminary design and formative evaluation design which was conducted on 50 junior high school students. Data collection techniques used are content validity by expert judgement and test. The instruments are expert assessment sheet and question sheet after content validity being conducted. Data analysis is done by finding the average of expert validation and learning achievement score. It is continued by comparing the score of validity and effectivity criteria. The results show that the student worksheets assisted by Liveworksheets and the developed mathematical problem-solving abilities are categorized as very valid and effective.